Neurocysticercosis - The first documented clinical case in Mozambique - Santos, M. (2004)
Neurocysticercosis is claimed to be endemic in some African countries. However no clinical case has been documented in Mozambique until now. We report the first clinical case of human neurocysticercosis in Mozambique, where we suspect that this disease is under-recognised.